A novel linear neutralizing epitope of hepatitis E virus. Issue 30 (9th July 2015) - Tang, Zi-Min; Tang, Ming; Zhao, Min; Wen, Gui-Ping; Yang, Fan; Cai, Wei; Wang, Si-Ling; Zheng, Zi-Zheng; Xia, Ning-Shao
Highlights A novel neutralizing epitope L2 of HEV was identified. The novel epitope is located in a.a. 423–437 of HEV pORF2. Epitope L2 is non-immunodominant in both infection and vaccination process. We displayed epitope L2 on HBc149 protein and constructed HBcL2 particles. Immunization with HBcL2 stimulated anti-HEV neutralization in vivo.